Answer to Question #280082 in Calculus for jay

Question #280082

a)     Determine the Laplace transforms of the following functions


(i) f(t) = t3-2t

(ii) f(t) = sin3t-e2t

(iii) f(t) = e2t sinh4t



b) Find the Laplace transform of the following

(i) f(t) = 3e-4t- 5e4t

(ii) f(t) = t sin 3t + cos 4t


find the inverse transform of

(i) F (s) = 2/3-1/2s-3

(ii) F (s) = 5s-8/s(s-4), using partial fractions.


1
Expert's answer
2021-12-16T11:21:46-0500

a)     

(i) "f(t) = t^3-2t"


"F(s)=L\\{t^3-2t\\}"

"=\\dfrac{6}{s^4}-\\dfrac{2}{s^2}"

ii) "f(t) = \\sin(3t)-e^{2t}"


"F(s)=L\\{\\sin(3t)-e^{2t}\\}"

"=\\dfrac{3}{s^2+9}-\\dfrac{1}{s-2}"

iii) "f(t) = e^{2t}\\sinh(4t)"


"F(s)=L\\{e^{2t}\\sinh(4t)\\}"

"=\\dfrac{4}{(s-2)^2-16}"

b)

(i) "f(t) = 3e^{-4t}- 5e^{4t}"


"F(s)=L\\{3e^{-4t}- 5e^{4t}\\}"

"=\\dfrac{3}{s+4}-\\dfrac{5}{s-4}"

(ii) "f(t) = t\\sin(3t)+\\cos(4t)"


"F(s)=L\\{ t\\sin(3t)+\\cos(4t)\\}"

"=\\dfrac{6s}{(s^2+9)^2}-\\dfrac{s}{s^2+16}"

c)

(i) "F (s) =\\dfrac{2}{3}-\\dfrac{1}{2s-3}"


"f(t)=L^{-1}\\{\\dfrac{2}{3}-\\dfrac{1}{2s-3}\\}"

"=\\dfrac{2}{3}\\delta(t)-\\dfrac{1}{2}e^{3t\/2}"

(ii) "F (s) =\\dfrac{5s-8}{s(s-4)}"


"\\dfrac{5s-8}{s(s-4)}=\\dfrac{A}{s}+\\dfrac{B}{s-4}=\\dfrac{A(s-4)+Bs}{s(s-4)}"

"s=0:-4A=-8=>A=2"

"s=0:4B=12=>B=3"

"f(t)=L^{-1}\\{\\dfrac{5s-8}{s(s-4)}\\}=L^{-1}\\{\\dfrac{2}{s}\\}+L^{-1}\\{\\dfrac{3}{s-4}\\}"

"=2+3e^{4t}"


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog